Linkages between the U.S. and Japanese stock markets: a bivariate garch-m analysis - Koutmos, Gregory; Theodossiou, Panayiotis (My University, 1994)
Early empirical studies found that the Japanese stock market was one of the least integrated, had many unique characteristics, and was relatively isolated from other national stock markets, e.g., Ripley (1973). However, the gradual liberalization of the Japanese product and capital markets has substantially changed this picture. The Tokyo Stock Exchange (TSE) is increasingly becoming one of the most important players in the international arena. Along with the New York Stock Exchange (NYSE), they are the largest in terms of capitalization, volume and shares listed, and are perhaps the most influential in the world. The general movement of stock prices on the NYSE and TSE receive considerable attention from the international press, portfolio managers, international mutual funds, and financial institutions, among others. Exploring the nature and degree of interdependence between the two stock exchanges is, therefore, an important task and of interest to both private and institutional investors.
Keywords: Finance; Stock markets; New York Stock Exchange